Strategi Perkembangan Kreativitas Anak Usia Dini Melalui Pemainan Eduktif Untuk Anak - Rohmah, Aulia; Mairianta, Beatriz; Sembiring, Claudia Cresensia Br; G, Gustiana (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research discusses the development of children's creativity through games which can increase children's creativity and can also help children to get to know the alphabet through games that they will later play. The aim of this research is to find out the development of children's creativity at Kindergarten Aulia school and how teachers can increase creativity in children so that teachers can later find out the factors that support and inhibit children's creativity at Kindergarten Aulia School. The research method used in this research is using observation and interview methods. The results of the research show that the games we have carried out can help children to recognize the alphabet and can increase creativity in children through these game activities.